Phase-1 clinical study of tadalafil administered for selective fetal growth restriction in twin pregnancy. (3rd April 2021) - Magawa, Shoichi; Nii, Masafumi; Tanaka, Hiroaki; Furuhashi, Fumi; Maki, Shintaro; Kubo, Michiko; Tanaka, Kayo; Kondo, Eiji; Ikeda, Tomoaki
Abstract: Background: Selective fetal growth restriction (sFGR) is a condition of twin pregnancy in which the development of one fetus is restricted, despite normal growth of the other fetus. A method of intrauterine therapy for sFGR does not currently exist. The only treatment for sFGR is to terminate the pregnancy before the FGR worsens. In twin pregnancies, maternal and intrauterine environments are common in both fetuses, thus a placental factor is considered the cause of FGR in fetuses. Tadalafil is a phosphodiesterase (PDE)-5 inhibitor that induces an increase in uterine blood flow by dilatation of blood vessels in cases of FGR with placental dysfunction, which improves FGR. Purpose: The aim of this study was to investigate the safety and maximum tolerated dose (MTD) of tadalafil administered for twin pregnancy (diamniotic-monochorionic twin or diamniotic-dichorionic twin). Methods: In this phase I, open-label, dose-escalation trial, sequential patient cohorts (3 + 3 dose-escalation design) for twin pregnancy received tadalafil (20 or 40 mg/d) as a single dose by oral administration from the day they were diagnosed with sFGR, defined as estimated fetal weight (EFW) < 3% tiles, that is, −1.8 SD the mean EFW for gestational age (GA) to unacceptable toxicity or the day of delivery. This study evaluated the safety of maternally administered tadalafil for sFGR, examining maternal, fetal, and neonatal adverse events. Maternal adverse events were graded on the basis of the Common Terminology Criteria for Adverse Events v4.0. Results: Six women with sFGR who were pregnant with twins were treated with tadalafil. There were no severe adverse events in either cohort, although the most common (≥3 patients) drug-related adverse events were headache and heart failure. The MTD of tadalafil among Japanese patients was 40 mg. Conclusions: Tadalafil has a manageable safety profile up to an MTD of 40 mg/d.